Twisting sliding mode control with adaptation: Lyapunov design, methodology and application. (January 2017) - Shtessel, Yuri B.; Moreno, Jaime A.; Fridman, Leonid M.
Abstract: A novel adaptive-gain twisting controller that is robust to the bounded disturbances with the unknown boundaries is proposed. The control algorithm is derived using the Lyapunov function technique. It is shown that an ideal or real second order sliding mode is established, and the adaptation algorithm does not overestimate the control gain. The efficacy of the proposed adaptive twisting control is experimentally verified on a mass–spring–damper system.